Factorial structure of the determinants of tourist stay in the biosafety protocol before Covid-19 - Cruz García Lirios (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
The reactivation of tourism had been studied from the influence of the habitus of transfer and stay, but with the health contingency this process was mediated by the information of the places with biosafety protocols. The objective of the present work was to contrast a model of the determinants of stay, considering the mediating variables of the information. A confirmatory, psychometric and cross-sectional study was carried out with a selection of 100 students from a public university in central Mexico. A factorial structure was found that explained 61% of the variance and established the intention to transfer as a predictor, suggesting the extension of the work towards biosafety protocols.